Contribution to the study of the mechanism of the hypotensive action of dihydroxycodeinone (Revista Española de Fisiología, 1951)
The mechanism of the hypertensor action of dihydroxicodeinone, employing a dosis of 1 mg. per Kg. in weight is studied.After the injection into the internal carotid artery, a mechanism, either central or reflex is admitted, and after the injection into the jugular andsaphena veins a reflex mechanism, starting from the sensitive zones of the outlet of the cavas and in the right auricle.Contribution to the study of the mechanism of the hypertensor action of dihydroxicodeinone.